2018
DOI: 10.1002/biot.201700740
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Continuous Manufacturing for Liposomal Drug Products

Abstract: Over the last several years, continuous manufacturing of pharmaceuticals has evolved from bulk APIs and solid oral dosages into the more complex realm of biologics. The development of continuous downstream processing techniques has allowed biologics manufacturing to realize the benefits (e.g., improved economics, more consistent quality) that come with continuous processing. If relevant processing techniques and principles are selected, the opportunity arises to develop continuous manufacturing designs for add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Depending on the choice of the pore size, this strategy can be applied to isolate the desired product from larger particles by allowing it to diffuse into the permeate stream or to purify the target product from smaller impurities when it is maintained in the retentate stream. Moreover, the same configuration can be applied for buffer exchange or for product concentration in the retentate stream . This flexibility, together with the short processing times, the scalability, and the adaptability to continuous operation, established TFF as the standard purification method for liposome production.…”
Section: Development Of Scalable Ev Purification Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the choice of the pore size, this strategy can be applied to isolate the desired product from larger particles by allowing it to diffuse into the permeate stream or to purify the target product from smaller impurities when it is maintained in the retentate stream. Moreover, the same configuration can be applied for buffer exchange or for product concentration in the retentate stream . This flexibility, together with the short processing times, the scalability, and the adaptability to continuous operation, established TFF as the standard purification method for liposome production.…”
Section: Development Of Scalable Ev Purification Processesmentioning
confidence: 99%
“…This flexibility, together with the short processing times, the scalability, and the adaptability to continuous operation, established TFF as the standard purification method for liposome production. These strengths make TFF also an advantageous unit operation for the large‐scale production of EVs, considering their comparable lipid bilayer membranes and structures . Moreover, the results obtained by Dimov and coworkers demonstrated that the shear stress on the filter does not alter the integrity of liposomes at optimal operational conditions, thus offering a gentler purification method in comparison with UC .…”
Section: Development Of Scalable Ev Purification Processesmentioning
confidence: 99%
“…Regarding quality assurance, liposomes, and drug delivery nanosystems in general are affected by production scalability, reproducibility, availability of equipment, expertise, stability of the incorporated bioactive molecule and long-term stability [17]. Moreover, it has been suggested that liposomal drug development can benefit from continuous manufacturing, a processing concept where raw materials constantly flow into a process and product constantly flow out that has been applied to produce biologics [18].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of antigen proteins into nanoparticles allows the transfer of biological properties to liposomes . To generate an effective vaccine to enhance immunity, not only materials but also methods of manufacturing must be considered: antigen type and dose; immunostimulatory adjuvant; formulation refinement; and the size, surface charge (anionic, cationic, or neutral), lamellarity, and homogeneity . Several factors to generate an immune response through antigen‐carrying nanoparticles must be compared .…”
Section: Introductionmentioning
confidence: 99%